2-Heptanol inhibits Botrytis cinerea by accelerating amino acid metabolism and retarding membrane transport - Wu, Fangfang; Wang, Haibo; Lin, Yankun; Qu, Zesheng; Zheng, Bin; Feng, Shun; Li, Xinguo (Frontiers in Plant Science, 2024)
During the postharvest storage of tomatoes, they are susceptible to infection by Botrytis cinerea, leading to significant economic losses. This study evaluated the antifungal potential of 2heptanol (2-HE), a volatile biogenic compound, against B. cinerea and explored underlying antifungal mechanism. The results indicated that 2-HE effectively suppressed the growth of B. cinerea mycelia both in vivo and in vitro and stimulated the activities of antioxidative enzymes, including superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) in tomatoes.Furthermore, 2-HE reduced spore viability, compromised membrane integrity, and resulted in increased levels of extracellular nucleic acids, protein content, and membrane lipid peroxidation.Transcriptomic analysis revealed that 2-HE disrupted the membrane transport system and enhanced amino acid metabolism, which led to intracellular nutrient depletion and subsequent B. cinerea cell death. Additionally, 2-HE treatment did not negatively impact the appearance or quality of the tomatoes. In conclusion, the findings of this study offer insights into the use of 2-HE as a biocontrol agent in food and agricultural applications.